2020
DOI: 10.3390/f11091003
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variations of the Wood Density and Fiber Dimensions of the Persian Oak Wood

Abstract: Persian oak (Quercus brantii Lindl.) is a valuable native species in Iranian forests with very limited availability of data on its wood properties. The objective of the current study was to determine the influence of altitude and slope on physical properties and fiber dimensions of Persian oak wood. In addition, the relationship among wood properties, site conditions (temperature and rainfall) and growth traits of trees (tree height, DBH, basal area, age, crown diameter, crown basal area, volume and annual dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Generally, an increase in tree growth was related to a slightly higher FL. Several previous studies have shown that FL increases with increasing tree growth [ 28 – 31 ]. In the present study, the genetic correlations between growth traits and FL were also positive at the six sites, indicating that triploid breeding of Populus not only improves the FL but also increases the tree growth.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, an increase in tree growth was related to a slightly higher FL. Several previous studies have shown that FL increases with increasing tree growth [ 28 – 31 ]. In the present study, the genetic correlations between growth traits and FL were also positive at the six sites, indicating that triploid breeding of Populus not only improves the FL but also increases the tree growth.…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that the combination of environmental and climatic factors affects tree growth and wood properties (Zobel, van Buijtenen 1989). Geographic factors (latitude, altitude, aspect and slope), climatic factors (temperature and humidity), biotic factors (humans, animals, plants and microorganisms) as well as soil properties can influence wood characteristics (Usta et al 2014;Kaygin et al 2016;Topaloglu et al 2016;Nazari et al 2020). Studies on the relationship between wood properties and ecological factors are of great importance in understanding wood applications as well as cre-https://doi.org/10.17221/125/2020-JFS ate a database for different wood species.…”
mentioning
confidence: 99%
“…The same author studied the correlation between the position in the growth ring by radius and the wood fibre length and showed a functional quadratic dependence. In some studies (Mladenova et al, 2017;Nazari et al, 2020) fibre characteristics have been investigated, mainly fibre length in the wood of different oak species. The results showed a great dependence of its dimensions on location conditions.…”
Section: Resultsmentioning
confidence: 99%